Vocabulary building and memory training android game - Ong, Yuh Kang, 1991-, author; Masitah Ghazali, supervisor; Fakulti Komputeran (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2014)
Project Paper (Sarjana Muda Sains Komputer (Kejuruteraan Perisian)) - Universiti Teknologi Malaysia, 2014